A puncture-resistant zinc-bromine flow battery separator, preparation method and application thereof

By using ultra-high molecular weight polyethylene and inorganic nanoparticles with intrinsic regular pore structure in the zinc-brominated flow battery separator, a multi-scale sponge body three-dimensional network structure is formed, which solves the problems of zinc dendrites, electrolyte cross-contamination and high cost of the separator, and improves the coulomb efficiency and service life of the battery.

CN119153742BActive Publication Date: 2025-03-18INST OF WENZHOU ZHEJIANG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411631703.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-18
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

In the process of commercialization, zinc bromine flow batteries face technical challenges such as zinc dendrites formation, electrolyte cross-contamination, low ion transmission efficiency and high cost of diaphragm materials, which affect their safety, life and economy.

Method used

A puncture-resistant zinc bromine flow cell separator is used to prepare a separator with a multi-scale sponge body three-dimensional network structure by mixing ultra-high molecular weight polyethylene, plasticizer, pore-making agent, color masterbatch, bromine-resistant agent and lubricant. The synergistic effect of inorganic nanoparticles with intrinsic regular pore structure and silica is used to reduce the average pore size of the separator, improve the bromine resistance ability and the Coulomb efficiency of the battery.

Benefits of technology

Effectively inhibit the growth of zinc dendrites, reduce cross-contamination of electrolytes, improve ion selectivity, reduce separator costs, extend battery service life, and improve battery coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153742B_ABST
    Figure CN119153742B_ABST
Patent Text Reader

Abstract

This application discloses a puncture-resistant zinc-bromine flow battery separator, its preparation method, and its application. The puncture-resistant zinc-bromine flow battery separator comprises the following raw materials: ultra-high molecular weight polyethylene, plasticizer, pore-forming agent, color masterbatch, bromine-resistant agent, and lubricant. The pore-forming agent consists of a first inorganic nanoparticle and a second inorganic nanoparticle, the second inorganic nanoparticle being an inorganic nanoparticle with an intrinsically regular pore structure. The zinc-bromine flow battery separator of this application selects the second inorganic nanoparticle with an intrinsically regular pore structure at the angstrom level. This second inorganic nanoparticle synergistically interacts with the first inorganic nanoparticle in the separator, jointly forming a multi-scale sponge-like three-dimensional network structure. This reduces the average pore size of the separator, which is beneficial for improving the bromine barrier capacity of the separator and increasing the coulombic efficiency of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of liquid flow batteries, and in particular to a puncture-resistant zinc-bromine liquid flow battery diaphragm, a preparation method and applications thereof. Background Art

[0002] As an advanced energy storage technology, zinc-bromine flow batteries have significant application potential in large-scale energy storage due to their high energy density, long life, scalability and environmental friendliness. They can provide stable and reliable power supply, and are particularly suitable for grid peak regulation, renewable energy storage, and power supply in remote areas. The efficient operation of zinc-bromine flow batteries is of great significance for achieving sustainable energy utilization and reducing carbon emissions.

[0003] Although zinc-bromine flow batteries have many advantages, their commercialization process still faces some technical challenges. Among them, the formation of zinc dendrites is one of the main problems, which may cause internal short circuits and diaphragm penetration in the battery, thus affecting the safety and life of the battery. In addition, cross-contamination of the electrolyte, low ion transfer efficiency and high cost of diaphragm materials are also key factors limiting their widespread application. Solving these problems is crucial to improving battery performance and reducing costs.

[0004] As the core component of zinc-bromine flow batteries, the performance of the diaphragm directly affects the efficiency and stability of the battery. Improving the diaphragm material can improve its chemical stability and mechanical strength, effectively inhibit the growth of zinc dendrites, reduce electrolyte cross-contamination, and improve ion selectivity. In addition, the development of cost-effective diaphragm materials is of great significance to reducing the overall cost of batteries and promoting their commercialization. Therefore, the improvement of the diaphragm plays an indispensable role in improving the performance and economy of zinc-bromine flow batteries and promoting their widespread application in the field of energy storage. Summary of the invention

[0005] The purpose of the present application is to provide a zinc-bromine flow battery separator that blocks the penetration of bromide ions and bromine complexes and resists the puncture of zinc dendrites.

[0006] To achieve the above objectives, the technical solution adopted in the present application is: to provide a puncture-resistant zinc-bromine flow battery separator, comprising the following preparation raw materials: ultra-high molecular weight polyethylene, a plasticizer, a pore-forming agent, a masterbatch, a bromine-resistant agent and a lubricant, wherein the pore-forming agent is composed of a first inorganic nanoparticle and a second inorganic nanoparticle, and the second inorganic nanoparticle is an inorganic nanoparticle with an intrinsic regular pore structure.

[0007] As a preference, the first inorganic nanoparticles and the second inorganic nanoparticles are mixed in a mass ratio of (7-9):(1-3) to obtain the pore-forming agent.

[0008] As another preference, the second inorganic nanoparticles are any one of or a combination of ZSM-5, ZSM-11, ZSM-12, ZSM-22, ZSM-23, ZSM-35, ZSM-48 model ZSM series molecular sieves, Y-type molecular sieves, MFI series molecular sieves, MCM-22, MCM-41, MCM-48 model MCM series molecular sieves.

[0009] As another preference, the second inorganic nanoparticles are molecular sieves having a silicon-aluminum structure.

[0010] As another preference, the first inorganic nanoparticles are composed of large-diameter particles and small-diameter particles, wherein the large-diameter particles have a diameter range of 50-100 nm, and the small-diameter particles have a diameter range of 7-50 nm.

[0011] As another preferred embodiment, the large-size particles and the small-size particles are mixed in a mass ratio of (3-4):(1-2) to obtain the first inorganic nanoparticles.

[0012] As another preference, the first inorganic nanoparticles are silicon dioxide.

[0013] As another preference, the molecular weight of the ultra-high molecular weight polyethylene is greater than 1 million.

[0014] A method for preparing a puncture-resistant zinc-bromine flow battery separator comprises the steps of uniformly mixing 25 to 50 parts of ultra-high molecular weight polyethylene, 35 to 65 parts of a plasticizer, 20 to 50 parts of a pore-forming agent, 1 to 20 parts of a masterbatch, 0.1 to 3 parts of a bromine-resistant agent and 1 to 5 parts of a lubricant to obtain a mixture, extruding the mixture through a twin-screw extruder, aging and drying the mixture to obtain the puncture-resistant zinc-bromine flow battery separator;

[0015] The pore-forming agent is obtained by mixing first inorganic nanoparticles and second inorganic nanoparticles in a mass ratio of (7-9): (1-3), the first inorganic nanoparticles are obtained by mixing large-size particles and small-size particles in a mass ratio of (3-4): (1-2), the first inorganic nanoparticles are silicon dioxide, and the second inorganic nanoparticles are molecular sieves.

[0016] A zinc-bromine liquid flow battery comprises any of the above-mentioned punctured zinc-bromine liquid flow battery separators, or the punctured zinc-bromine liquid flow battery separator prepared by the above-mentioned preparation method.

[0017] Compared with the prior art, the beneficial effects of this application are:

[0018] (1) The zinc-bromine liquid flow battery diaphragm of the present application selects the second inorganic nanoparticles with an intrinsic regular pore structure at the angstrom level, which produce a synergistic effect with the first inorganic nanoparticles in the diaphragm to jointly form a multi-scale sponge three-dimensional network structure, thereby reducing the average pore size of the diaphragm, which is beneficial to improving the bromine barrier capacity of the diaphragm and improving the coulombic efficiency of the battery.

[0019] (2) This application uses a certain ratio of large-size particles and small-size particles to mix, which has good bromine molecule blocking performance and resistivity;

[0020] (3) The present application uses ultra-high molecular weight polyethylene, which can improve the toughness of the membrane and enhance the puncture resistance of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the pore size distribution diagram of the functional membrane of the flow battery in Example 3 tested by the capillary method.

[0022] Figure 2 This is the pore size distribution diagram of the liquid flow battery membrane tested by the capillary method in comparative example 1.

[0023] Figure 3 This is the pore size distribution diagram of the functional membrane of the liquid flow battery in Example 3 tested by mercury intrusion testing.

[0024] Figure 4 This is the pore size distribution diagram of the flow battery diaphragm of Comparative Example 1 tested by mercury intrusion method.

[0025] Figure 5 This is the pore size distribution diagram of the gas-liquid method test of the functional membrane of the liquid flow battery in Example 3.

[0026] Figure 6 This is the pore size distribution diagram of the liquid flow battery membrane tested by the gas-liquid method in comparative example 1.

[0027] Figure 7 This is the pore size distribution diagram of the liquid-liquid method test of the functional membrane of the liquid flow battery in Example 3.

[0028] Figure 8 This is the pore size distribution diagram of the liquid-liquid method test of the liquid flow battery membrane in comparative example 1. DETAILED DESCRIPTION

[0029] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0030] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0031] The present application provides a puncture-resistant zinc-bromine flow battery separator, comprising the following preparation raw materials: ultra-high molecular weight polyethylene, a plasticizer, a pore-forming agent, a masterbatch, a bromine-resistant agent and a lubricant, wherein the pore-forming agent is composed of a first inorganic nanoparticle and a second inorganic nanoparticle, and the second inorganic nanoparticle is an inorganic nanoparticle with an intrinsic regular pore structure.

[0032] The present application selects second inorganic nanoparticles having an intrinsic regular pore structure at the angstrom level, which produce a synergistic effect with the first inorganic nanoparticles in the diaphragm to jointly form a multi-scale sponge three-dimensional network structure, thereby reducing the average pore size of the diaphragm, which is beneficial to improving the bromine barrier capacity of the diaphragm and improving the coulombic efficiency of the battery.

[0033] In some embodiments, the first inorganic nanoparticles are silicon dioxide, which can be silicon dioxide prepared by a gas phase method or silicon dioxide prepared by a precipitation method. Silicon dioxide has the property of absorbing oil.

[0034] In some embodiments, the first inorganic nanoparticles and the second inorganic nanoparticles are mixed in a mass ratio of (7-9):(1-3) to obtain a pore-forming agent.

[0035] Preferably, the first inorganic nanoparticles are composed of large-size particles and small-size particles, the large-size particles have a particle size range of 50-100 nm, and the small-size particles have a particle size range of 7-50 nm.

[0036] More preferably, the specific surface area of ​​the large-size particles is 100 to 200 m 2 / g, the specific surface area of ​​small-size particles is 150-380 m 2 / g.

[0037] More preferably, the large-diameter particles and the small-diameter particles are mixed in a mass ratio of (3-4):(1-2) to obtain the first inorganic nanoparticles.

[0038] The mixing ratio of large-size particles and small-size particles and the selection of particle size are based on many factors such as performance, cost and process. Too many large-size (greater than 50 nm) inorganic nanoparticles will increase the process time and energy loss during the extrusion process, and will also cause the average pore size of the prepared porous diaphragm to be larger, which will not be able to block the shuttle of bromine molecules, resulting in a decrease in battery performance such as coulomb efficiency; while too many small-size (less than 50 nm) inorganic nanoparticles will lead to excessively high raw material costs and high resistivity of the prepared diaphragm, resulting in a decrease in battery performance such as voltage efficiency.

[0039] The diaphragm of the present application uses both large-size particles and small-size particles during preparation, so that the inorganic nanoparticles are more evenly filled in multiple levels inside the diaphragm, avoiding the generation of a larger pore structure.

[0040] In some embodiments, the second inorganic nanoparticles are microporous molecular sieves with an intrinsic regular pore structure, including but not limited to ZSM-5, ZSM-11, ZSM-12, ZSM-22, ZSM-23, ZSM-35, ZSM-48 model ZSM series molecular sieves, Y-type molecular sieves, MFI series molecular sieves, MCM-22, MCM-41, MCM-48 model MCM series molecular sieves, any one or a combination of multiple thereof.

[0041] The present application improves the regularity of the internal pore structure of the porous membrane by compounding the microporous molecular sieve with an intrinsic regular pore structure with the first inorganic nanoparticle, which is beneficial to increase the through-hole ratio of the porous membrane and reduce its resistivity. Adding a microporous molecular sieve with an intrinsic regular pore structure in the preparation of the membrane can effectively reduce the proportion of the pore-forming agent in the porous membrane, increase the content of ultra-high molecular weight polyethylene in the membrane, and help enhance the puncture resistance of the membrane, providing ideas for solving the problem of zinc dendrites and zinc dead crystals that are easy to generate at the negative electrode of the battery.

[0042] Further preferably, the second inorganic nanoparticle is a molecular sieve containing a silicon-aluminum structure, and its pore size range is 0.1-2 nm. The molecular sieve containing a silicon-aluminum structure with negative charge is preferred, and after preparation, it will be evenly dispersed inside and on the surface of the porous membrane, and the principle of "like charges repel each other" can be used to further block the Br formed by the self-complexation of bromine molecules. 3- Br 5- The penetration of ions can improve the coulombic efficiency of the battery.

[0043] In some embodiments, the bromine-resistant agent is any one or more of ditetradecyl alcohol ester, bis(3,5-tert-butyl-4-hydroxyphenyl) sulfide, thioesters, didodecanol ester, phosphites, and dioctadecanol ester.

[0044] In some embodiments, the plasticizer is any one of lead-acid battery separator oil, paraffin oil, white oil, phthalate, adipic acid ester, and phosphate ester, or a combination of multiple thereof.

[0045] In some embodiments, the masterbatch includes, but is not limited to, a black masterbatch with light absorbing properties, a black masterbatch with reinforcing properties, a hydrophilic masterbatch with water absorbing properties, or a mixture of more thereof.

[0046] In some embodiments, the viscosity-average molecular weight of the ultra-high molecular weight polyethylene is greater than 1 million, preferably, the molecular weight is between 3 million and 9 million. Generally, the higher the molecular weight of the ultra-high molecular weight polyethylene, the higher the degree of cross-linking and entanglement between its molecular chains, which is conducive to improving the toughness of the material and enhancing the puncture resistance of the diaphragm; however, when the molecular weight of the polyethylene is too high, it is difficult to achieve uniform mixing with the inorganic nanoparticle pore-forming agent during the processing, resulting in a larger average pore size of the prepared diaphragm, which cannot play a role in blocking the shuttle of bromine molecules.

[0047] The present application also provides a method for preparing a puncture-resistant zinc-bromine flow battery diaphragm. According to parts by mass, 25 to 50 parts of ultra-high molecular weight polyethylene, 35 to 65 parts of plasticizer, 20 to 50 parts of pore-forming agent, 1 to 20 parts of masterbatch, 0.1 to 3 parts of bromine resistance agent and 1 to 5 parts of lubricant are uniformly mixed to obtain a mixture, and the mixture is extruded through a twin-screw extruder, and after aging and drying, a puncture-resistant zinc-bromine flow battery diaphragm of the present application is obtained.

[0048] Example 1

[0049] A puncture-resistant zinc-bromine flow battery separator was prepared according to the following ratio: 25 kg of ultra-high molecular weight polyethylene with a molecular weight of 3 million, 37 kg of plasticizer paraffin oil, 12 kg of silica with a particle size range of 50-100 nm, 8 kg of silica with a particle size range of 7-50 nm, 5 kg of molecular sieve ZSM-5, 10 kg of black masterbatch, 1 kg of bromine-resistant agent didodecanol ester and 2 kg of lubricant sodium stearate.

[0050] The above raw materials except the plasticizer were pre-mixed in a high-speed stirrer at a speed of 600 rpm for 10 min, and then the plasticizer was added and mixed at a speed of 300 rpm for 30 min to obtain a mixture, which was fed into a twin-screw extruder through a loss-in-weight scale for extrusion at a speed of 200 rpm, a barrel temperature of 190 °C, and a die temperature of 200 °C; aged at 25 °C for 10 h, extracted and dried at 60 °C to obtain a puncture-resistant zinc-bromine liquid flow battery separator.

[0051] Example 2

[0052] The addition amount of large-size particles in the raw material is adjusted to 9 kg, the addition amount of small-size particles is adjusted to 6 kg, and the molecular sieve is adjusted to 10 kg. The other formulas and preparation steps are consistent with Example 1.

[0053] Example 3

[0054] The molecular weight of the ultra-high molecular weight polyethylene in the raw material was adjusted to 5 million, and the other formulas and preparation steps were consistent with Example 2.

[0055] Comparative Example 1

[0056] The molecular sieve was removed from the original formula, and the addition amount of small-size particles was adjusted to 10 kg and the addition amount of large-size particles was adjusted to 15 kg. The other formulas and preparation steps were consistent with Example 2.

[0057] Comparative Example 2

[0058] A puncture-resistant zinc-bromine flow battery separator was prepared according to the following ratio: 25 kg of ultra-high molecular weight polyethylene with a molecular weight of 3 million, 37 kg of plasticizer paraffin oil, 15 kg of silica with a particle size range of 7-50 nm, 10 kg of molecular sieve ZSM-5, 10 kg of black masterbatch, 1 kg of bromine-resistant agent didodecanol ester and 2 kg of lubricant sodium stearate.

[0059] Comparative Example 3

[0060] A puncture-resistant zinc-bromine flow battery separator was prepared according to the following ratio: 25 kg of ultra-high molecular weight polyethylene with a molecular weight of 3 million, 37 kg of plasticizer paraffin oil, 15 kg of silica with a particle size range of 50-100 nm, 10 kg of molecular sieve ZSM-5, 10 kg of black masterbatch, 1 kg of bromine-resistant agent didodecanol ester and 2 kg of lubricant sodium stearate.

[0061] Comparative Example 4

[0062] Silicon dioxide was removed from the original formula, and the amount of molecular sieve added was adjusted to 25 kg. Other formulas and preparation steps were consistent with Example 2.

[0063] Comparative Example 5

[0064] The molecular weight of the ultra-high molecular weight polyethylene was adjusted to 300,000, and the other formulas and preparation steps were consistent with those in Example 2.

[0065] Performance Testing

[0066] The puncture-resistant zinc-bromine flow battery membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to pore size test, resistivity test, puncture resistance test and oxidation coefficient test, respectively, and the performance test results are recorded in Table 1 below.

[0067] The oxidation coefficient test is based on the mass change test method of standard NB / T 4216-2018. Specifically, the membrane is cut into 2 cm × 2 cm square samples with a cutter; the sample is placed in a 70 ° C oven for drying, accurately weighed and recorded as m1; the dried membrane is placed in a beaker of saturated bromine water to ensure that the membrane is completely immersed; the beaker is then placed in a 60 ° C water area for heating, kept at a constant temperature for 3 hours, the membrane is taken out, and rinsed with deionized water; the rinsed membrane is placed in a 70 ° C oven for drying, and accurately weighed again and recorded as m2. The oxidation coefficient is calculated according to the following formula:

[0068]

[0069] Table 1 Formulas and performance test results of various embodiments and comparative examples

[0070]

[0071] By analyzing Examples 1 to 3, adjusting the proportion of the second inorganic nanoparticles and adjusting the molecular weight of polyethylene have different effects on the performance of the prepared zinc-bromine liquid flow battery membrane, and a membrane with a smaller pore size and better puncture resistance can be obtained. When used in zinc-bromine liquid flow batteries, the service life of the battery can be extended.

[0072] In Comparative Example 1, while maintaining the total mass of the pore-forming agent and the mass ratio of small-size particles to large-size particles unchanged, no second inorganic nanoparticles were added to the formula, and the pore size of the obtained flow battery diaphragm was larger, which could not achieve the effect of blocking bromine.

[0073] Comparative Examples 2 and 3 similarly maintain the total mass of the pore-forming agent and the mass of the second inorganic nanoparticles unchanged, and adjust the first inorganic nanoparticles to use either all small-sized particles or all large-sized particles. The resistivity of the diaphragm made entirely of small-sized particles is too high, and the battery performance is reduced; while the diaphragm made entirely of large-sized particles has a relatively large pore size and a poor ability to block bromine.

[0074] In Comparative Example 4, the first inorganic nanoparticles are not added, and the total mass of the pore-forming agent is kept unchanged. The resulting diaphragm has a large pore size, high resistivity, and poor puncture resistance, and is not suitable for use in a zinc-bromine flow battery system.

[0075] In Comparative Example 5, under the condition that the formula quality remains unchanged, only the polyethylene with a molecular weight of 3 million is adjusted to polyethylene with a molecular weight of 300,000. The pore size of the diaphragm obtained is larger and the puncture resistance performance is also poor.

[0076] The performance of Example 3 was further compared with that of Comparative Example 1. The capillary method, mercury injection method, gas-liquid method and liquid-liquid method were used to test the pore size of Example 3 and Comparative Example 1. In the liquid-liquid method test of the diaphragm, the infiltrated liquid was isobutanol, and the displacement liquid was a saturated solution of isobutanol and deionized water. The diaphragm was cut into pieces with a diameter of 40 mm using a cutter, and placed in the test cavity. The cavity was gradually pressurized, and the pressure P and the flow rate L of the displacement liquid were accurately recorded. The pressure corresponding to the intersection of the semi-dry line and the wet line was the pressure of the average pore size. Then, the pressure data was converted into pore size data according to the capillary conversion formula to obtain the average pore size. The results of the pore size test are recorded in Table 2.

[0077] Figure 1 and Figure 2 The capillary method test pore size distribution diagrams of Example 3 and Comparative Example 1 are respectively, Figure 3 and Figure 4 The pore size distribution diagrams of the mercury intrusion method test of Example 3 and Comparative Example 1 are respectively, Figure 5 and Figure 6 The pore size distribution diagrams of the gas-liquid method test of Example 3 and Comparative Example 1 are respectively, Figure 7 and Figure 8 The pore size distribution diagrams of the liquid-liquid method test of Example 3 and Comparative Example 1 are shown respectively.

[0078] Table 2 Aperture test results of Example 3 and Comparative Example 1

[0079]

[0080] The average pore size of the diaphragm of Example 3 under various test methods is smaller than that of Comparative Example 1, and the proportion of blind holes and macropores is significantly reduced, indicating that the multi-level compounding of high and low particle size inorganic nanoparticles of the present invention reduces the proportion of blind holes and macropores, and filling with molecular sieves with a regular pore structure can effectively reduce the average pore size of the diaphragm.

[0081] The zinc-bromine liquid flow battery diaphragm of the present application effectively improves the puncture resistance and oxidation resistance of the diaphragm, provides a solution to the problems of zinc dendrites and zinc dead crystals, and reduces the pore size of the diaphragm by compounding high and low particle size inorganic nanoparticles and molecular sieves with regular pore structures. At the same time, the electronegativity of the molecular sieve is utilized, such as a molecular sieve with a silicon-aluminum structure, to enhance the ability of the diaphragm to block bromine shuttling, improve the coulombic efficiency of the battery, and help to extend the service life of the zinc-bromine liquid flow battery, thereby promoting the rapid development of zinc-bromine liquid flow batteries in the field of long-term energy storage.

[0082] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. A puncture-resistant zinc-bromine flow battery separator, characterized in that: The invention comprises the following raw materials: ultra-high molecular weight polyethylene, a plasticizer, a pore-forming agent, a masterbatch, a bromine-resistant agent and a lubricant, wherein the pore-forming agent is formed by mixing a first inorganic nanoparticle and a second inorganic nanoparticle in a mass ratio of (7-9): (1-3), the second inorganic nanoparticle is a molecular sieve with a silicon-aluminum structure, and the first inorganic nanoparticle is silicon dioxide; the first inorganic nanoparticle is composed of large-size particles and small-size particles, wherein the large-size particles have a particle size range of 50-100 nm and the small-size particles have a particle size range of 7-50 nm; the molecular weight of the ultra-high molecular weight polyethylene is greater than 1 million, the large-size particles and the small-size particles are mixed in a mass ratio of (3-4): (1-2) to obtain the first inorganic nanoparticle; the raw materials are uniformly mixed to obtain a mixture, the mixture is extruded through a twin-screw extruder, and the puncture-resistant zinc-bromine liquid flow battery separator is obtained after aging and drying.

2. A method for preparing a puncture-resistant zinc-bromine flow battery membrane, characterized in that: 25-50 parts of ultra-high molecular weight polyethylene, 35-65 parts of plasticizer, 20-50 parts of pore-forming agent, 1-20 parts of masterbatch, 0.1-3 parts of bromine resistance agent and 1-5 parts of lubricant are uniformly mixed to obtain a mixture, and the mixture is extruded through a twin-screw extruder, aged and dried to obtain the puncture-resistant zinc-bromine flow battery separator; The pore-forming agent is obtained by mixing first inorganic nanoparticles and second inorganic nanoparticles in a mass ratio of (7-9): (1-3), the first inorganic nanoparticles are obtained by mixing large-size particles and small-size particles in a mass ratio of (3-4): (1-2), the first inorganic nanoparticles are silicon dioxide, the second inorganic nanoparticles are molecular sieves with a silicon-aluminum structure, the large-size particles have a particle size range of 50-100 nm, and the small-size particles have a particle size range of 7-50 nm; the molecular weight of the ultra-high molecular weight polyethylene is greater than 1 million.

3. A zinc-bromine flow battery, characterized in that: It comprises the puncture-resistant zinc-bromine liquid flow battery separator according to claim 1, or the puncture-resistant zinc-bromine liquid flow battery separator prepared by the preparation method according to claim 2.

Citation Information

Patent Citations

  • Zinc-bromine flow battery diaphragm applicable to laser welding, and preparation method thereof

    CN103618057A

  • Composite-structure gel polymer electrolyte for lithium battery and preparation method and application thereof

    CN113889663A

  • Composite bipolar plate for zinc-bromine flow battery as well as preparation method and application of composite bipolar plate

    CN115995572A

  • Porous composite separator incorporated with inorganic particles, electrochemical device comprising the same, and method of preparing the separator

    KR1020150050498A